Addressing virtual reality misclassification: A hardware‐based qualification matrix for virtual reality technology. (27th June 2021) - Takac, Marcel; Collett, James; Conduit, Russell; De Foe, Alexander
Abstract: Through its unique sensory synchronized design, virtual reality (VR) provides a convincing, user‐centred experience of highly controllable scenarios. Importantly, VR is a promising modality for healthcare, where treatment efficacy has been recognized for a range of conditions. It is equally valuable across wider research disciplines. However, there is a lack of suitable criteria and consistent terminology with which to define VR technology. A considerable number of studies have misclassified VR hardware (e.g. defining laptops as VR), hindering validity and research comparisons. This review addresses these limitations and establishes a standardized VR qualification framework. As a result of a comprehensive theoretical and literature review, the hardware‐based VR qualification matrix is proposed. The matrix criteria consist of (1) three‐dimensional (3D) synchronized sensory stimulation; (2) degrees of freedom tracking; and (3) visual suppression of physical stimuli. To validate the model and quantify the current scale/diversity of VR misclassification, a 2019 sectional review of health‐related studies was conducted. Of the 115 studies examined against standardized criteria, 35.7% utilized VR, 31.3% misclassified VR, 18.3% were considered quasi‐VR, and 14.8% omitted critical specifications. The proposed model demonstrates good validity and reliability for qualifying and classifying VR. Key Practitioner Messages Virtual reality (VR) therapy has gained rapid empirical support, although many practitioners do not understand the difference between genuine and less‐realistic VR variations. That has resulted from an evident lack of suitable criteria to define VR across a range of studies and protocols. Our proposed hardware‐based virtual reality qualification matrix addresses issues to do with misclassification, via the introduction of standardised criteria. Applying the matrix to existing literature has revealed that more than 30% of VR studies use hardware that does not fit the high standards of rigour required for immersion in a simulated space. The model is a practical tool researchers and practitioners can use to quality and verify VR standards across research studies.